Diversity of quantitative, qualitative, and vitamin C content characteristics in F5 generation of Capsicum baccatum - HILDA ADINA RAHMI; MUHAMAD SYUKUR; DEWI SUKMA; SYARIFAH IIS AISYAH (Society for Indonesian Biodiversity, 2024)
Abstract. Rahmi HA, Syukur M, Sukma D, Aisyah SI. 2024. Diversity of quantitative, qualitative, and vitamin C content characteristics in F5 generation of chili pepper Capsicum baccatum species. Biodiversitas 25: 2878-2886. Chili is a popular vegetable worldwide, and Indonesia is one of the largest chili producers. However, the cultivation of Capsicum baccatum species is still uncommon in Indonesia. This study aimed to assess the diversity and heritability of yield and yield quality of F5 populations of C. baccatum. This study was conducted at the Experimental Field of Perumahan Alam Sinar Sari, Bogor. The experiment followed a randomized complete block design (RCBD) using 12 genotypes with three replications and four sample plants per replication. The F5 populations of the following genotypes were used: 4k-6p, 4k-7p, 7m-4q, 2m-2m, 7m-3q, 7m-3m, 7m-2q, 2m-2q, 7m-8m, 7m-1m, Bishop Crown, and Lemon Drop. The observations included quantitative, qualitative character,vitamin C contents, and soluble solids. The results showed that the fruit weight per plant ranged from 37.73 to 94.24 grams, while the number of fruits per plant ranged from 11.46 to 30.95. Fruit length ranged from 2.65 to 6.08 cm, and fruit diameter ranged from 15.70 to 41.43 mm. The weight per fruit ranged from 3.43 to 14.89 grams. Brightness or L* values ranged from 19.06 to 41.93, a* values ranged from 5.62 to 31.49, and b* values ranged from 22.90 to 57.45. The chroma value ranged from 30.87 to 64.20, and the hue value ranged from 46.54 to 80.23. The analysis of vitamin C content showed a range of 12.20 to 17.74 mg/20 g, and the test results of soluble solids ranged from 8.77% to 13.49%. All quantitative characters showed high heritability, indicating a strong genetic influence on these characters. The qualitative observations were analyzed, and the results showed that the 12 C. baccatum chilies had similarity coefficients ranging from 0.0 to 0.5. The similarity analysis resulted in grouping the 12 genotypes of C. baccatum into four main groups.